2016
DOI: 10.2527/jas.2016-0431
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide association study of methane emissions in Angus beef cattle with validation in dairy cattle1

Abstract: Methane (CH) is a product of enteric fermentation in ruminants, and it represents around 17% of global CH emissions. There has been substantial effort from the livestock scientific community toward tools that can help reduce this percentage. One approach is to select for lower emitting animals. To achieve this, accurate genetic parameters and identification of the genomic basis of CH traits are required. Therefore, the objectives of this study were 1) to perform a genomewide association study to identify SNP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
48
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 41 publications
8
48
1
2
Order By: Relevance
“…Another option, then, is to look at methane intensity, defined as liters of CH 4 related to output [e.g., kg milk (for dairy) or meat (for sheep or beef) produced], or at methane yield, defined as liters of CH 4 related to input (e.g., per kg of DMI). Residual methane production, defined as observed minus predicted CH 4 production, has also been suggested for use (Herd et al, 2014;Berry et al, 2015;Manzanilla Pech et al, 2016). Residual methane production is based on the same concept as residual feed intake (RFI), where the phenotype of interest is regressed for each factor that influences this phenotype.…”
Section: Possible Direct Phenotypesmentioning
confidence: 99%
“…Another option, then, is to look at methane intensity, defined as liters of CH 4 related to output [e.g., kg milk (for dairy) or meat (for sheep or beef) produced], or at methane yield, defined as liters of CH 4 related to input (e.g., per kg of DMI). Residual methane production, defined as observed minus predicted CH 4 production, has also been suggested for use (Herd et al, 2014;Berry et al, 2015;Manzanilla Pech et al, 2016). Residual methane production is based on the same concept as residual feed intake (RFI), where the phenotype of interest is regressed for each factor that influences this phenotype.…”
Section: Possible Direct Phenotypesmentioning
confidence: 99%
“…De Haas et al [7] reported that the estimated heritability of predicted methane emission (PME) per milk production and PME per milk production corrected for fat and protein content were 0.35 and 0.58, respectively. Moreover, genome-wide association studies (GWAS) have identified several single nucleotide polymorphisms (SNPs) associated with the measured or predicted rate of methane emission in Holstein cattle [7] and Angus cattle [8]. Thus, genetic selection can be employed to reduce PME per unit of milk production.…”
Section: Introductionmentioning
confidence: 99%
“…Cattle have a considerable ability to produce high-quality proteins from non-edible plant cell wall components for human consumption [16]. However, it is well established that gastrointestinal microbiota contributes to feed digestion and enteric methane emission in ruminants [17][18][19][20], as approximately 17% of global methane emissions generated through ruminants [8]. Methane emission is a difficult and expensive trait to measure and is not routinely measured in dairy cattle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic background of CH4 emission has been studied before in beef and dairy cattle Manzanilla-Pech et al, 2016). No specific regions of the genome were found to be significantly associated in the GWAS on CH4 emission predicted with feed intake in 665 dairy cows .…”
Section: Genetic Background Of Ch4 Emissionmentioning
confidence: 99%